2016
DOI: 10.4314/ahs.v15i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and factors associated with delayed initiation of breastfeeding among mothers who deliver in Mulago hospital, Uganda.

Abstract: Background: Breastfeeding as a determinant of infant health and nutrition saves up to 1.5 million infant lives annually. Though breastfeeding is mostly universal in sub-Saharan Africa, early initiation of breastfeeding is rarely practiced. Objective: To determine magnitude and factors associated with delayed initiation of breastfeeding among mother-infant pairs who deliver in Mulago hospital. Methods: We carried out a descriptive cross sectional study, where 665 mother-infant pairs were interviewed within 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
52
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 14 publications
16
52
3
Order By: Relevance
“…This association has also been observed in other studies done in Uganda, Nigeria and Vietnam [12,26,35]. The practice of separating the newborn from the mother immediately after caesarean delivery could partly explain this delay [36].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…This association has also been observed in other studies done in Uganda, Nigeria and Vietnam [12,26,35]. The practice of separating the newborn from the mother immediately after caesarean delivery could partly explain this delay [36].…”
Section: Discussionsupporting
confidence: 78%
“…Another community survey done in Eastern Uganda showed that only 51% of mothers initiated breastfeeding immediately after birth [24]. This proportion is, however, different from another study done at the national referral hospital, which found a much higher proportion of almost 70%, of mothers initiating breastfeeding early [12]. The difference could be explained by the policies at the national referral hospital or differences in the populations studied.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations